Development of SCAR marker for Thai fragrant rice (Oryza sativa L. var.indica cv. Pathumthani 1) mutants induced by low energy ion beam - Kanta Sangwijit (2018)
Seeds of Thai fragrant rice (Oryza sativa L.var. indica cv. Pathumthani 1) were bombarded by nitrogen ions at a 60 keV energy level with ion fluences of 6 and 8×10 16 ion/cm 2 for induction mutation. After the 5 th generation, a number of mutants were obtained including EPOS1, EPOS2, EPOS3, TPOS1, TPOS2, EBPOS1 and EBPOS3. These mutants showed several improved characteristics including a tall variety and an early flowering variety. Moreover, the seed shape and pericarp color of the mutants were different from the control. In order to determine the scope of genetic variation for these mutants, a HAT-RAPD (High Annealing Temperature-RAPD) analysis was used to investigate the genome of these mutants. From a total of 110 arbitrary primers, one primer named OPAA14 produced a unique candidate fragment at a molecular size of 700 bp and presented only in the EBPOS3 mutant. This fragment was selected for sequencing and conversion to the more reproducible and robust Sequence Characterized Amplified Region (SCAR) marker. PCR amplification using the SCAR marker revealed a 300 bp fragment only in the EBPOS3 mutant. Since new lines or varieties of fragrant rice with modified phenotypes are often developed from their progenitors, the use of SCAR marker is a useful tool for identification purposes for right protection. This technique is a cost-effective and morphologically independent way to identify such mutants.